DOING IT WHEN OTHERS DO: A STRATEGIC MODEL OF PROCRASTINATION - Claudia Cerrone (Economic Inquiry, 2021)
This paper develops a strategic model of procrastination in which present-biased agents prefer to perform an onerous task with someone else. This turns their decision of when to perform the task into a procrastination game—a dynamic coordination game between present-biased players. The model characterizes the conditions under which interaction mitigates or exacerbates procrastination. A procrastinator matched with a worse procrastinator may perform her task earlier than she otherwise would: she wants to avoid the increased temptation that her peer's company would generate. Procrastinators can thus use bad company as a commitment device to mitigate their self-control problem. (JEL C72, C73, D03, D91)
Keywords: 330